Menanamkan Nilai-Nilai Kearifan Lokal Pada Pembelajaran IPS Di Sekolah Dasar - Aleta Brinje; Bernadethe Peni Hera; Jesika Imut; Neni Alviani; Sastawati Sastawati; Budi Kurnia (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study examines the integration of local wisdom values ​​in Social Studies (IPS) learning in Elementary Schools (SD) as an effort to strengthen students' character and cultural identity. Then the low utilization of local wisdom in IPS learning, which results in students' lack of understanding of regional cultural values. The purpose of this study is to analyze the application of local wisdom values ​​in IPS learning and identify its impact on students' understanding and character. The method used is a qualitative approach with literature study techniques by collecting a number of information obtained from various sources and media to learn about the application of local wisdom if applied to IPS learning in Elementary Schools. The results of the study indicate that the integration of local wisdom values, such as mutual cooperation, deliberation, and environmental wisdom, can increase student involvement and strengthen a sense of love for local culture and this confirms that IPS learning based on local wisdom is not only relevant to the socio-cultural context of students but also effective in forming characters rooted in the nation's culture. The conclusion of this study is that the integration of local wisdom in social studies learning in elementary schools can be a significant educational strategy in building students' social understanding and character values, so it needs to be supported by educational policies that encourage the implementation of local culture-based materials in elementary schools.